Esensi Ajaran Bhujangga dalam Tradisi Ritual Masyarakat Batur: (Kajian Teologi Hindu) - Gunawijaya, I Wayan Titra (Jayapangus Press, 2025)
Batur is seen as one the centers of Balinese civilization, which a strategic position in the spread of Hinduism in Bali. Bhujangga teachings are one of the sources the implementation yajna for the Batur community, in the developing mythology Ida Bhujangga is a human who is diksa to become a sulinggih, which until now still exists with the name Ida Bhattara Bhujangga. This study aims to determine Bhujangga teachings in Batur in the implementation of rituals and to determine the concept of Hindu Theology from these teachings. The study uses a qualitative descriptive approach with data collection techniques through participatory observation, semi-structured interviews with Batur traditional figures, temple caretakers Pura Tuluk biyu, and text documentation studies. The results of the study explain that Bhujangga teachings emphasize the implementation yajna ceremonies as an implementation of maintaining balance between humans and nature through the application of dharma teachings, one of which is the Madewasraya ceremony at Pura Tuluk Biyu Batur. Ida Pandita Bhujangga achieved an increase in status from human to bhattara who is worshipped by the Batur community through the Ida Bhattara Bhujangga shrine, reflecting the concept of Hindu Theology. The existence of the Ida Bhattara Bhujangga Shrine and Pratima in the Tuluk Biyu Batur Temple is the embodiment Saguna Brahman. This study confirms that the Bhujangga teachings in Batur are not only in the order mythology but also in the material order both in the form Pratima, Pelinggih, and the implementation yajna as the embodiment of the Hindu Theology in the Batur.